2018
DOI: 10.1080/14712598.2018.1494719
|View full text |Cite
|
Sign up to set email alerts
|

Smoking reduces the efficacy of belimumab in mucocutaneous lupus

Abstract: We observed a negative impact of smoking on the efficacy of belimumab in mucocutaneous SLE. In contrast, no impact of smoking on belimumab efficacy was seen in patients with articular manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 44 publications
0
26
0
7
Order By: Relevance
“…One previous paper has also shown the potential advantages of specific musculoskeletal outcome measures in patients treated with belimumab [36]. The CLASI and joint counts have also revealed nuances of response in individual organ domains in patient subgroups after belimumab therapy [37].…”
Section: Discussionmentioning
confidence: 99%
“…One previous paper has also shown the potential advantages of specific musculoskeletal outcome measures in patients treated with belimumab [36]. The CLASI and joint counts have also revealed nuances of response in individual organ domains in patient subgroups after belimumab therapy [37].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of belimumab on serum levels of anti-double stranded (ds)DNA antibodies and BAFF, as well as the homologous to BAFF plasma cell survival factor a proliferation-inducing ligand (APRIL), have been demonstrated in previous studies [2][3][4]. Furthermore, predictors of response and non-response to belimumab treatment have been implicated; high disease activity and anti-dsDNA positivity at baseline have been associated with increased probability of good response, whereas established organ damage, especially in the cardiovascular and neuropsychiatric domains, has been shown to reduce belimumab efficacy [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 94%
“…Two response thresholds were initially selected to screen factors for each analysis. These included standard thresholds, representing relative decreases in CLASI-A (≥50%) or CLASI-D (≥20%) within the range of outcomes considered in prior studies,8 14–16 19 and stringent thresholds, representing larger relative decreases in CLASI-A (≥75%) or CLASI-D (≥40%) score.…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies have found four-point or 20% decrease in CLASI-A score on a 70-point scale to be indicative of noticeable clinical improvement 13. Despite the possibility that such modest changes may be less meaningful for patients with more severe involvement or may fail to distinguish treatment response from expected clinical variability, similar thresholds have been used to classify activity improvement in interventional and observational studies 8 14. Other endpoints used include larger relative changes in CLASI-A scores (eg, 50% improvement in CLASI-A),15 16 analogous to the Psoriasis Area Severity Index (PASI) percentage change endpoints common in psoriasis studies (eg, PASI50) 17.…”
Section: Introductionmentioning
confidence: 99%